Penyuluhan Kesehatan Reproduksi Remaja Menggunakan Kombinasi Media Poster, Leaflet, dan Celemek Organ Reproduksi - Terry Y.R. Pristya; Chahya Kharin Herbawani; Ulya Qoulan Karima; Arnur Oktafiyanti; Nadia Ramadhanty (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
This program activity was using a counseling method that aimed was provided education or information about adolescent reproductive health and the risk of it. The media has used a combination of the poster, leaflet, and apron of reproductive organs. This counseling was conducted among 18 adolescents in RW 07 Cipayung Village, Depok. The result of this counseling was an increase in the average score of knowledge before and after counseling by 22.8% (an increase in the average score from 7.1 to 8.9). Statistical results using the Wilcoxon test show that the combination of the three media counseling also affects changes in the average score of adolescent knowledge on reproductive health. Suggestions to further increase the knowledge of participants, the poster media used for counseling is in larger paper size, so that it can be seen more clearly by all participants